Трудности диагностики в протитуберкулезном стационаре при отсутствии бактериовыделения - Гусарова, А. Ю.; Просветов, Ю. В.; Коваленко, Е. А.; Gusarova, А. Yu.; Prosvetov, Yu. V.; Kovalenko, О. A.; Гусарова, Аліна Юріївна; Просвєтов, Юрій Васильович (My University, 2019)
A clinical case of conducting a diagnostic searching a patient with suspected recurrence of pulmonary tuberculosis in the absence of bacterial excretion is presented in the article.
Diagnostic difficulties in tuberculosis hospital at the bacterial excretion absence
Keywords: tuberculosis; cancer; diagnostics